The Effects of Mesenchymal Stem Cells on Oral Cancer and Possible Therapy Regime - Yang, Tong; Tang, Shuai; Peng, Shan; Ding, Gang (Frontiers in Genetics, 2022)
Mesenchymal stem cells (MSCs) are characterized by self-renewal, rapid proliferation, multipotent differentiation, and low immunogenicity. In addition, the tropism of MSCs towards injured tissues and tumor lesions makes them attractive candidates as cell carriers for therapeutic agent delivery and genetic material transfer. The interaction between tumor cells and MSCs in the tumor microenvironment plays an important role in tumor progression. Oral cancer is one of the most common malignant diseases in the head and neck. Although considerable improvements in the treatment of oral cancer were achieved, more effective and safer novel agents and treatments are still needed, and deeper studies on the etiology, pathology, and treatment of the oral cancer are desirable. In the past decades, many studies have reported the beneficial effects of MSCs-based therapies in the treatment of various diseases, including oral cancers. Meanwhile, other studies demonstrated that MSCs may enhance the growth and metastasis of oral cancer. In this paper, we reviewed the research progress of the effects of MSCs on oral cancers, the underlying mechanisms, and their potential applications in the treatment of oral cancers.